Berberis jiuzhaigouensis (Berberidaceae), a new riparian shrub from northern Sichuan, China - Hong-Li Pan; Yue Zhang; Jia-Hao Wang; De-Chang Meng; Chih-Chieh Yu (PhytoKeys)
Berberis jiuzhaigouensis is herein described as a new deciduous species endemic to riparian habitats in Jiuzhaigou, northern Sichuan, China. Phylogenetic analyses based on complete plastome sequences and 322 nuclear loci consistently recover B. jiuzhaigouensis as a distinct and divergent lineage, genetically separated from all morphologically similar species and most closely related to B. gilgiana. Species delimitation analyses employing both topology-based (SODA) and substitution-based (bPTP, mPTP) frameworks further corroborate its taxonomic distinctiveness. This discovery highlights previously overlooked species diversity within Berberis in the Hengduan Mountains region.